Family‐provider consensus outcomes for children with medical complexity. (10th December 2018) - Fayed, Nora; Guttmann, Astrid; Chiu, Allison; Gardecki, Meghan; Orkin, Julia; Hamid, Jemila S; Major, Nathalie; Lim, Audrey; Cohen, Eyal
Abstract : Aim: To describe the process of obtaining consensus of outcome priorities between families of children with medical complexity (CMC) and their healthcare providers (HCPs) for the purpose of evaluating changes to service delivery. Method: The consensus of outcomes involved surveying families of CMC and HCPs and an in‐person consensus meeting. Priorities were obtained from the survey using a stratified ranking approach ensuring equal representation among unequally sized subgroups. An in‐person meeting was held using the survey results to inform Delphi voting. Results: Families of CMC ( n =40) and HCPs ( n =74) responded to the survey. Consensus generated three main target areas (child health, family health, experience of care) covered by 15 specific outcomes needed to evaluate care. Differences between family and HCP perceptions of importance were found for child self‐care, play, social skills, and recreation as well as emotional health (for both parent and child) outcomes. Interpretation: Families of CMC and HCPs identified common priorities for outcome evaluation of CMC initiatives. Outcomes that differ in importance between families of CMC and HCPs should be studied further. What this paper adds: Families of children with medical complexity and their providers can reach consensus on important outcomes. Stratifying subgroups ensures diverse representation, which is important to outcome prioritization. What this paper adds: Families of children with medical complexity and their providers can reach consensus on important outcomes. Stratifying subgroups ensures diverse representation, which is important to outcome prioritization. This article is commented on by Brosco on page 1000 of this issue. This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. Resumen: Consenso en los objetivos entre la familia y los profesionales de la salud para niños con complejidad médica: Objetivo: Describir el proceso para lograr un consenso sobre los objetivos prioritarios entre las familias de niños con complejidad médica (NCCM) y los profesionales de la salud (PS) con el fin de evaluar cambios en la prestación de servicios. Metodo: La búsqueda del consenso en los objetivos involucró una encuesta a las familias de NCCM y PS y luego una reunión en persona para lograr un consenso. Se identificaron las prioridades en la encuesta utilizando una clasificación estratificada para garantizar una representación equitativa entre los subgrupos de tamaño desigual. Luego se llevó a cabo una reunión en persona, utilizando los resultados de la encuesta para crear una votación tipo Delphi. Resultados: Las familias de NCCM (n = 40) y los PS (n = 74) respondieron a la encuesta. El consenso generó tres áreas principales (salud del niño/a, salud familiar, experiencia de atención) cubiertas por 15 resultados específicos necesarios para evaluar la atención. Se encontraron diferencias en la percepción de importancia de los objetivos entre la familia y los profesionales de la salud en las áreas del autocuidado del niño, el juego, las habilidades sociales y la recreación, así como los objetivos para la salud emocional (tanto para padres como para niños). Interpretación: Las familias de NCCM y los PS identificaron prioridades comunes para la evaluación de resultados de iniciativas para hacer cambios en la atención médica. Las diferencias entre los objetivos de las familias de NCCM y PS deben estudiarse con más detalle. Abstract : Resultados consensuais entre família‐profissional para crianças com complexidade médica: Objetivo: Descrever o processo de obter consenso dos resultados prioritários entre famílias de crianças com alta complexidade médica (ACM) e profissionais de saúde (PSs) para avaliar mudanças na prestação de serviços. Método: A obtenção de consenso dos resultados envolvidos foi obtida entrevistando ACMs e PSAs e por meio de um encontro pessoalmente. Prioridades foram obtidas a partir da entrevista usando uma pontuação estratificada assegurando representação igual entre grupos com tamanhos diferentes. Um encontro pessoalmente aconteceu usando os resultados da pesquisa para informar a votação Delphi. Resultados: Famílias de AMCs ( n =40) and PSs ( n =74) responderam às questões. O consenso gerou três áreas principais (Criança, família, experiência de cuidado) cobertas por 15 resultados específicos necessários para avaliar o cuidado. Diferenças entre percepções da família e de PSs e as percepções de importância foram obtidas para auto‐cuidado da criança, brincar, habilidades sociais, e recreação, assim como saúde emocional (para pais e filhos). Interpretação: Famílias de AMCs e PSs identificaram prioridades comuns para avaliacão de resultados em iniciativas de ACM. Resulados que diferem em importância entre famílias de AMCs e PSs devem ser considerados em futuros estudos